Uso racional de antiinflamatorio no esteroideo mediante dosis unitaria en el Hospital María Lorena Serrano Aguilar. - Chavez Ibañez, Maria Magdalena (2017)
Hippocrates was the Greek doctor most illustrious of antiquity, regarded as the father of medicine, prescribed extracts of the leaves of willow bark to reduce inflammation and fever. Nonsteroidal anti-inflammatory drugs are the pharmacological group that the population consumes mostly prescribed by the physician for the treatment of inflammatory pain and fever pictures. In the Ecuador prescribed ibuprofen and diclofenac, ketorolac to children and women in work of parto-cesarea within the system of drug unit dose, which controls the process that must have the drug from its correct prescription until his administration with the correct dose. Despite this there are flaws that arise within this system, such as errors in prescribing, dispensing/distribution and management, in the field of hospital pharmacy. The objective of this research id demonstrate the rational use of medication nonsteroidal anti-inflammatory drugs that are administered to patients in the Hospital Maria Lorena Serrano in the areas of Gynecology and Pediatrics, through the application of unit-dose to verify the correct procedure for the same. An observational research study was conducted the biochemist responsible for the preparation of unit dose in the areas of gynaecology and paediatrics; In addition jointly pre professional practices allowed to know the role of the biochemist in hospital pharmacy. A comparative study on the rational use of ketorolac, ibuprofen and diclofenac between two basic hospitals in the cantons of El Guabo and passage was finally developed. The results were: In the studied quarter showed that 87% of prescriptions were prescribed properly and 13% were prescribed incorrectly in the area of Pediatrics. In Gynecology, 81% of prescriptions were prescribed properly, and 19% were improperly prescribed. Nonsteroidal anti-inflammatory drugs in Pediatrics were not ketorolac with 15% and ibuprofen with 85%; in Gynecology ketorolac with 52%, with 36% diclofenac and ibuprofen with 12%. The rational use of these nonsteroidal anti-inflammatory drugs in Hospital Maria Lorena Serrano was 71% rational and irrational 29% and at the San Vicente de Paúl, was 85% rational and irrational 15%. It was demonstrated that the application of the system of unit, despite being dose carried out by professionals of the health of El Guabo canton hospital María Lorena Serrano, remain errors at the time of the prescription of the medication from the doctor. Factors that delay the process of the unit dose system and lead to errors at the time of the medication. In the areas of gynaecology and paediatrics nonsteroidal anti-inflammatory drugs used to treat post-operative aren't ketorolac, diclofenac and ibuprofen which are within the basic national box and conform to the needs of the inpatient. The lack of health professionals is an element that causes less fluidity in the unit dose system. Make more training María Lorena Serrano hospital health professionals, so that they are aware of the work being done in unit dose drug distribution system and understand the benefits that it brings to the hospital and therefore the hospitalized patient. Refuel the best way and possible readiness of missing medication at the pharmacy. Implement the hospital unit dose system María Lorena Serrano dose shared the same which would bring economic benefits to the State and to the rational use of medicines. Implement more health to hospital personnel to avoid medication errors. Further critical judgement and strengthen interventions made by the pharmaceutical biochemist in hospital pharmacy.